ANALISIS EFEKTIVITAS SISTEM MANAJEMEN KEAMANAN DI PERUSAHAAN SHOPEE DALAM MENINGKATKAN PROTEKSI DATA - Daffa Maulana Asviara; Ega Jerliana, Farel Ihsan Aditya, Adrian Rizky Pratama, Rifky Tri Nugroho (ADISAM PUBLISHER, 2024)
In the ever-growing digital era, e-commerce has become an important part of everyday life. Shopee is one of the largest and most popular platforms in Southeast Asia. With its growth, concerns about data and transaction security arise. The aim of this research is to evaluate how well Shopee's security system protects user data and ensures transaction integrity, as well as finding potential weaknesses and providing recommendations for improvement. The methodology used to do this is to conduct literature research on the Shopee Security Management System. The research results show that Shopee's security system protects user data well, but there are weaknesses that may need to be fixed. To continue to improve the security of their information system, Shopee regularly carries out risk evaluations and evaluations. So, Shopee maintains user trust, manages risks well, and uses a holistic approach to managing and improving data security.